2020
DOI: 10.1016/j.celrep.2020.107531
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Allosteric and Selective Inhibitors of the Molecular Chaperone TRAP1

Abstract: Highlights d Analysis of TRAP1 dynamics allows discovery of paralogselective allosteric inhibitors d Small molecules targeting TRAP1 revert TRAP1-dependent succinate dehydrogenase inhibition d Allosteric TRAP1 inhibitors abolish tumorigenic growth of neoplastic cells d Selective targeting of TRAP1 activity provides new antagonists of chaperones

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
92
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 71 publications
(93 citation statements)
references
References 59 publications
1
92
0
Order By: Relevance
“…The chaperone activity of TRAP1 is enhanced by its ERK-mediated phosphorylation (Masgras et al, 2017a), and dysregulated activation of Ras/ERK signalling is mandatory for the malignant growth of a variety of cancer types, including highly aggressive pancreatic adenocarcinoma and malignant peripheral nerve sheath tumors, where we show that TRAP1 has a dramatic inhibitory effect on SDH activity (this study and (Sanchez-Martin et al, 2020b). Hence, the possibility of targeting TRAP1 with great precision unlocks the doorway to the development of therapeutic approaches in neoplastic conditions where the metabolic rewiring that it orchestrates is critical for malignant cell viability.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…The chaperone activity of TRAP1 is enhanced by its ERK-mediated phosphorylation (Masgras et al, 2017a), and dysregulated activation of Ras/ERK signalling is mandatory for the malignant growth of a variety of cancer types, including highly aggressive pancreatic adenocarcinoma and malignant peripheral nerve sheath tumors, where we show that TRAP1 has a dramatic inhibitory effect on SDH activity (this study and (Sanchez-Martin et al, 2020b). Hence, the possibility of targeting TRAP1 with great precision unlocks the doorway to the development of therapeutic approaches in neoplastic conditions where the metabolic rewiring that it orchestrates is critical for malignant cell viability.…”
Section: Discussionsupporting
confidence: 63%
“…Here we find that TRAP1 is highly expressed at the beginning of fish embryogenesis, when it exerts an important bioenergetic role. As previously reported in tumor models (Guzzo et al, 2014, Kowalik et al, 2016, Masgras et al, 2017a, Sanchez-Martin et al, 2020a, Sanchez-Martin et al, 2020b, Sciacovelli et al, 2013, TRAP1 inhibits SDH activity during early Zebrafish development, crucially contributing to a bioenergetic phenotype characterized by low levels of OXPHOS. Absence of TRAP1 causes a delay in early development; this defect is gradually lost during the passage from embryo to larva stages, when oxygen tension increases and TRAP1 levels progressively decline.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…7A). TRAP1 is the mitochondrial paralog of the heat shock protein 90 (HSP90) family and is widely recognized as a potential anti-cancer drug target across multiple human malignancies, including leukemia [43][44][45][46][47][48][49] . Given that ATPase activity is required for TRAP1 function 50 , we hypothesized that ETS inhibition in leukemic mitochondria exposed to ΔG ATP may be driven by acute activation of TRAP1.…”
Section: Resultsmentioning
confidence: 99%
“…We have recently used a molecular dynamics-based strategy to identify an allosteric pocket distal to the ATPase site of TRAP1, which allowed the rational design and testing of small molecule compounds that target it (157). We have also found that the same allosteric domain can host the bis-dichloroacetate ester of the vegetal derivative honokiol DCA (HDCA) (158).…”
Section: Allosteric Inhibitorsmentioning
confidence: 99%